An Individual Level Test of the "Feminization of Poverty" Hypothesis: Evidence from Ghana. Issue 1 (March 2014) - Owusu-Afriyie, John; Nketiah-Amponsah, Edward
Feminization of poverty is a hypothesis that postulates that women experience poverty at higher rates than men. Over the years, empirical examination of this hypothesis has relied on the comparison between poverty status of female-headed and male-headed households due to lack of gender disaggregated data in many household surveys. However, the use of poverty among female-headed households as a representative measure of women's poverty masks the extent of poverty among women. Hence, this study uses individual gender disaggregated data from the Ghana Living Standards Surveys IV and V (GLSS IV and V) and the Foster–Greer–Thorbecke (FGT) classes of poverty measure to empirically test the "feminization of poverty" hypothesis in Ghana. The study also finds out whether this hypothesis is affected by the education level of the individual. The article finds that "feminization of poverty" is prevalent at all three levels of FGT poverty measures. The result further indicates that when education is taken into consideration, "feminization of poverty" is found to be prevalent only amongst the no education and primary education cohorts while masculinization of poverty is rather found among the secondary and tertiary education cohorts. Generally, in terms of the dynamic changes in "feminization of poverty, " the study finds that over the last two sets of surveys (GLSS IV and V), the phenomenon has reduced. Based on the results, we recommend that measures that target education as a tool for combating poverty should be strengthened amongst females whilst non-educational tools for combating poverty should target males.